Fluvoxamine: A Review of Its Mechanism of Action and Its Role in COVID-19 - Sukhatme, Vikas P.; Reiersen, Angela M.; Vayttaden, Sharat J.; Sukhatme, Vidula V. (Frontiers in Pharmacology, 2021)
Fluvoxamine is a well-tolerated, widely available, inexpensive selective serotonin reuptake inhibitor (SSRI) that has been shown in a small, double-blind, placebo-controlled, randomized study to prevent clinical deterioration of patients with mild coronavirus disease 2019 (COVID-19). Fluvoxamine is also an agonist for the sigma-1 receptor and through it is thought to control inflammation. We review here a body of literature that shows important mechanisms of action of fluvoxamine and other SSRIs that could play a role in COVID-19 treatment. These effects include: reduction in platelet aggregation, decreased mast cell degranulation, interference with endolysosomal viral trafficking, regulation of inositol-requiring enzyme 1α-driven inflammation and increased melatonin levels, which collectively have a direct antiviral effect, regulate coagulopathy or mitigate cytokine storm, known hallmarks of severe COVID-19.